Fabrication of Antibacterial Nanofibers Composites by Functionalizing the Surface of Cellulose Acetate Nanofibers. Issue 4 (24th January 2020) - Khan, Muhammad Qamar; Kharaghani, Davood; Sanaullah,; Shahzad, Amir; Duy, Nam Phan; Hasegawa, Yohei; Azeemullah,; Lee, Jungsoon; Kim, Ick Soo
Abstract: The surface modification of nanofibers web enables the invention of wound dressings by using the simple materials substrate without altering the mechanical properties of foundation materials or nanofibers web. Herein, authors fabricated the novel antibacterial wound dressings by functionalizing the surface of cellulose acetate (CA) nanofibers. This surface treatment was done through facile method. The silver sulfadiazine (SSD) nanoparticles were successfully synthesized on the surface of cellulose acetate nanofibers web by in‐situ facile method in which nanofibers webs were immersed in the solution of sodium sulfadiazine salt and silver nitrate (AgNO3 ) for three different interval of times (hrs). The resultant CA/SSD nanofibers were characterized by scan electron microscope, transmission electron microscope, FT‐IR, XPS, XRD, water contact angle and antibacterial agar disc diffusion test. All characterization results supported that this composite can be used for antibacterial wound dressings, especially for gram negative E. Coli bacteria because SSD has great potential against E. Coli bacteria. Abstract : The silver sulfadiazine (SSD) nanoparticles were successfully synthesized on the surface of cellulose acetate nanofibers web by in‐situ facile method in which nanofibers webs were immersed in the solution of sodium sulfadiazine salt/silver nitrate (AgNO3 ). All characterization results supported that this composite can be used for antibacterial wound dressings due to excellent antibacterial properties against gram negative E. coli, which is unique properties of SSD for antibacterial activity.